(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Because fast changing climate facilitates the movement of viruses as well as their hosts, also vectors, from one nation or region to another, early and correct identification of plant viruses is critical to their management. The diagnosis of viral diseases is becoming increasingly crucial. So because indications of viral infections are not always distinct and might be mistaken with those of abiotic stressors, a suggestive diagnosis may not be the best approach. Agriculture is vital to every country’s economy, and bacteria, fungus, and viruses represent a major danger to crops. Viruses, unlike any other ailment, are to blame for a significant share of the reduction in agricultural production. A variety of diagnostic procedures can be used to identify these viruses. There are direct and indirect solutions to this problem, each with its own set of benefits and drawbacks. The infection of the causative pathogen can be used to create diagnostic procedures. Observation of signals in indicator crops, electron microscopy, or serological techniques including such enzyme-linked Immunosorbent Assay have all been sometimes used identify virus in plants. They can be used to identify the best timing to start utilizing ELISA or PCR assays to detect plant viruses. Plant viruses can be recognized and treated if found early enough, result in a virus-free crop in the future. These techniques (ELISA or PCR) will become the future standards in diagnostics as the cost of these techniques (ELISA or PCR) decreases.